Characterization and comparative genomics analysis of RepA_N multi-resistance plasmids carrying optrA from Enterococcus faecalis - Zhang, Enbao; Zong, Shuaizhou; Zhou, Wei; Zhou, Jinzhi; Han, Jianzhong; Qu, Daofeng (Frontiers in Microbiology, 2023)
This research aimed to investigate the antibiotic resistance of Enterococcus faecalis from swine farms in Zhejiang Province and the prevalence and transmission mechanism of oxazolidone resistance gene optrA. A total of 226 Enterococcus faecalis were isolated and their resistance to 14 antibiotics was detected by broth microdilution. Results showed that the antibiotic resistance rate of 226 isolates to nearly 57% (8/14) of commonly used antibiotics was higher than 50%. The resistance rate of tiamulin was highest (98.23%), that of tilmicosin, erythromycin, tetracycline and florfenicol was higher than 80%, and that of oxazolidone antibiotic linezolid was 38.49%. The overall antibiotics resistance in Hangzhou, Quzhou and Jinhua was more serious than that in the coastal cities of Ningbo and Wenzhou. The result of PCR showed that optrA was the main oxazolidinone and phenicols resistance gene, with a detection rate of 71.68%, and optrA often coexisted with fexA in the isolates. Through multi-locus sequence typing, conjugation transfer, and replicon typing experiments, it was found that the horizontal transmission mediated by RepA_N plasmid was the main mechanism of optrA resistance gene transmission in E. faecalis from Zhejiang Province. Two conjugative multi-resistance plasmids carrying optrA, RepA_N plasmid pHZ318-optrA from Hangzhou and Rep3 plasmid from Ningbo, were sequenced and analyzed. pHZ318-optrA contain two multidrug resistance regions (MDR), which contributed to the MDR profile of the strains. optrA and fexA resistance genes coexisted in IS1216E-fexA-optrA-ferr-erm(A)-IS1216E complex transposon, and there was a partial sequence of Tn554 transposon downstream. However, pNB304-optrA only contain optrA, fexA and an insertion sequence ISVlu1. The presence of mobile genetic elements at the boundaries can possibly facilitate transfer among Enterococcus through inter-replicon gene transfer. This study can provide theoretical basis for ensuring the quality and safety of food of animal origin, and provide scientific guidance for slowing down the development of multi-antibiotic resistant Enterococcus.